Zintegrowane systemy informacyjno-analityczne w realizacji systemów controllingu w małych i średnich przedsiębiorstwach - Sierocki, Robert (Integrated Information-Analytical Systems (IIAS) in Controlling Systems for Small and Medium Enterprises (SME)., 2006)
The integration of information systems is an important issue of assurance of high IT efficiency level in business. It is especially important in HAS which support controlling systems. Unfortunately, many tools that are the best to integrate analytical systems cost too much for an average SME to be implemented. Then some organization procedures can be useful.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1101, s. 153-160